Architecture and key terminal technologies of 5G-based internet of vehicles. (October 2021) - Wang, Yang; Ning, Wei; Zhang, Shengyu; Yu, Hao; Cen, Hongjie; Wang, Sunan
Abstract: Cellular Vehicle-to-Everything technology (C-V2X) is one of the important technical means to fulfill the Internet of Vehicles (IoV) services. Several standards organizations around the world have carried out research on C-V2X key technologies, network architectures and service application scenarios. The development of the IoV has put forward more requirements for 5G broadband mobile networks in terms of high bandwidth, low latency, high concurrency, low power consumption, and heterogeneous network compatibility. This paper attempts to study the IoV architecture and key terminal units such as on-board unit (OBU) design and road side unit (RSU) based on 5G and C-V2X technology. It first introduces the development of IoV technology and standards, and analyzes the existing IoV architecture design. The vehicle OBU design and RSU service design were finally proposed and described in detail.